Electrochemical simulation of psychotropic drug metabolism compared to in vivo processes using liquid chromatography and mass spectrometry - Jerszyńska, Paulina; Szultka-Młyńska, Małgorzata (Frontiers in Pharmacology, 2025)
IntroductionPsychotropic drugs strongly affect the human psyche through their ability to modulate the neurotransmitter activity and to treat mental disorders and diseases. Monitoring of psychotropic drugs in clinical studies is significant. Thus. establishing methodologies for analyzing these drugs and their pharmacologically active metabolites in biological matrices is essential for patients’ safety. Therefore, therapeutic drug monitoring (TDM) of these drugs in patients receiving pharmacotherapy in psychiatric hospitals is necessary to avoid medical complications, psychiatric adverse effects, or poisoning. In addition to TDM, the main factor in pharmacokinetics that should be monitored along with the drug is its metabolic pathway. The literature on transformation products (TPs) resulting from the psychotropic drug degradation is limited. Hence, to investigate the potential TPs of target compounds, electrochemistry (EC) and liver microsome assays were used to generate TPs, which were further characterized using liquid chromatography-tandem mass spectrometry (LC-MS/MS). The results obtained by EC-(LC)-MS and liver microsome assays were compared with conventional in vivo studies by analyzing biological samples (human plasma) from patients.MethodsThe electrochemical mimicry of the oxidative phase I and II metabolism was achieved in a thin-layer cell equipped with a boron-doped diamond (BDD) working electrode under controlled potential conditions. Structures were proposed for the electrochemically generated products based on the MS/MS experiments. Moreover, in order to examine the proposed metabolic pathways of target compounds, the incubation with human liver microsomes was applied. Additionally, a sensitive, specific, and rapid LC-MS/MS method was developed and validated to quantify selected drugs and their metabolites in biological samples. The preparation of biological samples was accomplished through microextraction by a packed sorbent (MEPS). Finally, the results from LC-MS/MS analysis of biological samples, liver microsomes and electrochemical TPs were compared to evaluate the quality of electrochemical metabolism mimicry.Results and discussionData from in vivo experiments agreed with the data from electrochemical oxidation, which predicted some of the potential metabolites found in the human liver microsomes. EC–(LC)-MS is well-suited for the simulation of the oxidative metabolism of selected psychotropic drugs and acts as the orthogonal source of information about drug metabolites compared to liver microsomes and biological matrices. EC-(LC)-MS enables the direct identification of reactive TPs, circumvents time-consuming sample preparation and is ethically advantageous because it reduces the need for animal experiments.